Rapid transition to home omalizumab treatment for chronic spontaneous urticaria during the COVID-19 pandemic: A patient perspective - Catherine King (Elsevier, 2021)
Efforts to reduce non-urgent hospital attendances during the COVID-19 pandemic have been the focus of much attention from healthcare professionals worldwide. In Ireland, due to funding constraints omalizumab is only available for hospital-based administration. Fifty-eight patients with chronic spontaneous urticaria and angioedema (CSU) receiving omalizumab in our centre were rapidly transitioned to home self-administration at the start of the pandemic. We conducted an anonymised patient survey after 3 months of home therapy with the aim of characterizing the patient experience throughout this period. 41 patients participated in our questionnaire (71% response rate). 93% of patients favored self-injection of omalizumab from home, with respondents citing cost savings, time savings, improved flexibility, fewer hospital visits, and less risk of exposure to COVID-19 infection as particular benefits. Concerns regarding home administration including injecting incorrectly, forgetting a dose, or having a reaction were reported very infrequently. Eighty-three percent (83%) of patients wished to continue with home therapy long-term. This survey highlights broadly positive experiences for patients rapidly transitioning to home omalizumab administration. This data will be useful to inform healthcare funders in decisions regarding patient-centred care in CSU. Facilitating home omalizumab therapy in suitable CSU patients should be strongly considered in the post-pandemic setting.